(untitled) (Italiano LinguaDue, 2023)
Il contributo si concentra sull’analisi del modo in cui i termini ‘multilinguismo’ e ‘plurilinguismo’ sono utilizzati nei documenti di politica linguistica europea, e sulle loro implicazioni per l’educazione linguistica. In tali documenti, anche molto recenti, è presente ancora una forte oscillazione dell’uso e del significato dei due termini, che contribuisce a condizionate la concreta applicazione pratica dell’educazione plurilingue, come intesa da De Mauro (1975) e dalle Dieci Tesi GISCEL. From GISCEL Theses to european multi-(?)-linguistic policy documents: same challenges in different contexts The paper focuses on analyzing the way the terms ‘multilingualism’ and ‘plurilingualism’ are used in European language policy documents, and their implications for language education. In such documents, even very recent ones, there is still a strong fluctuation in the use and meaning of the two terms, which contributes to conditioning the concrete practical application of ‘plurilingual education’, as conceived by De Mauro (1975) and the Dieci Tesi GISCEL.